Fluoride in Chicken (Gallus domesticus) Feathers from Nakuru, Kenya - Gudima, V. O.; Wambu, E. W.; Lagat, G.; Waddams, K. E. (Africa Environmental Review Journal, 2021)
Fluoride (F) toxicity in avian species has elicited global attention. To study the fluoride risks in chicken domesticated in Nakuru County of Kenya, maize and water samples were considered as potential sources of fluoride excessive intake while feathers gave an indication of fluoride body burden. The fluoride concentrations were measured and correlated to the levels in the poultry water, chicken feathers and in maize samples obtained from farms where the poultry was reared. The resulting data indicated a fluoride concentrations range of 10.4 ± 3.5 to 20.2 ± 3.5 mg/kg in the maize sampless, whereas in chicken feathers the fluoride levels ranged from 6.3 ± 2.4 to 16.6 ± 8.4 mg/kg. The F concentration in poultry water (0.4 ± 0.5 to 2.8 ± 2.2mg/L), was correlated to those in chicken feathers and the results showed that poultry water was major contributing factor to overall F exposure of farm birds. It was observed that labile F from high altitude areas percolated and polluted water and biological systems down- slope at distances controlled by the slope of land. For this reason, the areas at the rift valley floor were at greatest risk of fluoride toxicity